COMPOSITION, AGE AND GEODYNAMIC POSITION OF ALKALINE ROCKS IN THE BORGOY AND BOTSY MASSIFS (DZHIDA ALKALINE PROVINCE) - I. A. Izbrodin; A. G. Doroshkevich; V. B. Khubanov; E. A. Khromova (Геодинамика и тектонофизика)
The Borgoy and Botsy massifs are a part of the Dzhida alkaline province of the Western Transbaikalia. It has been stated that the rocks of the Borgoy massif were formed during the period from 246 to 243 Ma, which coincides with the formation period of the Permian-Triassic alkaline magmatic rocks common in the Vitim province. The age obtained from the zircons in the Botsy massif (121±1.0 Ma) is typical of the final stage of the transformation of the rocks related to rifting and alkali basalt lava flow. The presence of negative Nb-Ta anomaly and a relative enrichment in Rb, Ba, Sr and U imply interaction between the material of the plume and the earlier accretionary complexes of the subduction zones.